Cardiovascular Magnetic Resonance Findings Late After the Arterial Switch Operation. (September 2016) - Shepard, Charles W.; Germanakis, Ioannis; White, Matthew T.; Powell, Andrew J.; Co-Vu, Jennifer; Geva, Tal
Abstract : Background—: Despite its robust diagnostic capabilities in adolescents and adult patients after the arterial switch operation, little information is available on the cardiovascular magnetic resonance findings in this population. Methods and Results—: The cardiovascular magnetic resonance findings of 220 consecutive patients evaluated in our center were retrospectively reviewed (median age at cardiovascular magnetic resonance, 15.4 years; 66.8% male sex). Compared with published normal values, left and right ventricular end-diastolic volume z scores were mildly enlarged (0.48±1.76 and 0.33±1.5; P =0.0003 and 0.0038, respectively), with 26% of patients having left ventricular dilatation and 20% having right ventricular dilatation. Left ventricular dysfunction was present in 21.5% of patients (mild in most), and only 5.1% of patients had mild right ventricular dysfunction. Myocardial scar was found in 1.8% of patients. Dilatation of the neoaortic root was common (76%), and root z score increased at an average rate of 0.03 points per year. By multivariable analysis, neoaortic root dilatation was associated with worse neoaortic valve regurgitation (OR, 5.29; P =0.0016). The diameters of the thoracic aorta distal to the root were near-normal in most patients, whereas the neomain pulmonary artery was typically oval shaped with decreased anteroposterior and normal lateral diameters. Conclusions—: Although the majority of arterial switch operation patients have normal ventricular size and function and myocardial scar is rare, an important minority exhibits ventricular enlargement or dysfunction. Neoaortic root dilatation, which is present in most patients and progresses over time, is strongly associated with significant neoaortic valve regurgitation. The findings of this study provide reference values against which arterial switch operation patients can be compared with their peers.